Dramatic and persistent loss of eyelashes. (5th June 2015) - Venneuguès, Rowena Vicencio; Macbeth, Abby; Levell, Nick J
Although most paediatric hair loss presenting to clinicians is due to alopecia areata, unusual patterns should prompt a careful history.